Atmospheric Linke Turbidity Index over Deukhuri Valley, Dang - Shrestha, P. M.; Gupta, S. P.; Joshi, U.; Chapagain, N. P.; Karki, I. B.; Poudyal, K. N. (Journal of Nepal Physical Society, 2022)
The aim of this project is to study Atmospheric Linke turbidity index over Deukhuri Valley, Dang (27°50’32.2" N, 82°45’41.9" E and 445 m a. s. l.). The atmospheric Linke Turbidity index is calculated from solar radiation measurements of NASA satellite for period of 4 years (2015, 2016, 2017, 2018). The annual average clearness index (KT ), Linke turbidity index (LT ) and visibility are 0.55 ± 0.12, 2.5 ± 1.1 and 10.4 ± 3.8 km respectively. Atmospheric Linke turbidity index is used on agriculture, hydrology, climate change and energy harvesting. In study period, number of good days (visibility > 15 km) and number of bad days (visibility < 5 km) are found to be 188 and 94 respectively. This research work is beneficial for the further identification, impact and analysis of atmospheric turbidity at different places.